Comment pratiquer la théologie trinitaire en pèlerin ? - Durand, Emmanuel (Revue des sciences philosophiques et théologiques, 2008)
Towards qualifying Trinitarian theology as a theology of pilgrims, one must wonder about the relation between Trinitarian theology and eschatological beatitude. Yet one ought to begin by clarifying the objective correlation between divine beatitude and the Trinitarian mystery. The following question then presents itself: how is one to interpret in the Summa Theologiae the unnoticed sequence between the last question on the divine essence, consecrated to divine beatitude, and the first question on the Trinity, consecrated to the two Trinitarian processions? Towards negotiating as well as possible this delicate passage, it is necessary to analyze the epistemological disagreement between Thomas Aquinas and Richard of St. Victor over the status of « reasons » in Trinitarian theology